Evaluación de la capacidad de adaptación al estrés climático en Quercus mediterráneos: ¿plasticidad fenotípica o variación genotípica? (V Congreso Forestal Español, 2009)
Los factores de estrés asociados al clima representan el principal factor limitante en el crecimiento de las plantas. Muchos de ellos se traducen en la generación de daños fotooxidativos. Para evitarlos, las plantas presentan un conjunto de mecanismos denominados de fotoprotección que se inducen en respuesta a factores estresantes ambientales. Sin embargo, no está claro si la potencialidad de expresión del sistema fotoprotector depende exclusivamente de la plasticidad fenotípica de cada especie o de su procedencia (genotipo). En el presente trabajo, se estudió la respuesta fotoprotectora en varias poblaciones ibéricas de encina (Quercus ilex L.). Se muestrearon tres localidades con tres tipos de climas mediterráneos muy contrastados: Alcubierre en Huesca (semiárido-continental); Soria (continental) y Tertanga en Álava (oceánico). A lo largo del año 2008 se estimó el crecimiento secundario de 10 árboles adultos por localidad y se muestrearon hojas del año, en primavera, verano e invierno. Estos resultados se compararon con los obtenidos en plántulas de bellotas procedentes de las tres localidades. Se determinaron diversos parámetros indicativos del nivel de fotoprotección y funcionamiento fotosintético: contenidos de pigmentos fotosintéticos y tocoferoles, pubescencia foliar, y eficiencia fotosintética. En el campo, las encinas de Tertanga presentaron el máximo crecimiento secundario y los menores niveles de tocoferoles, pubescencia y reflectancia foliar. El menor crecimiento se registró en Soria, donde se observó un proceso de fotoinhibición invernal que también se dio en Alcubierre en menor medida. En el invernadero, las plántulas de Alcubierre mostraron los mayores niveles en el ratio xantofilas del ciclo VAZ respecto a clorofila (VAZ/cl), pubescencia, y reflectancia foliar. Estos resultados sugieren la coexistencia de mecanismos fotoprotectores fisiológicos de gran plasticidad en Q. ilex, en parte dependientes de la procedencia de las poblaciones, con otros intrínsecos de tipo morfológico determinados genotípicamente. Palabras

Photoprotection in evergreen Mediterranean plants during sudden periods of intense cold weather (Trees-Structure and …, 2003)
The photoprotective responses to an abrupt period of exceptional cold weather were studied in several Mediterranean evergreen species with different ecological requirements. The same pattern of response was observed in most of the species with little change in hydrophilic antioxidants (ascorbate and glutathione) and the carotenoid pool, an increase in the content of a -tocopherol, and a night retention of de-epoxidised xanthophylls (antheraxanthin and zeaxanthin). The accumulation of these xanthophylls correlated with a sustained decrease in maximal photochemical efficiency (Fv/Fm). This reduction in the rate of electron transport would reduce the production of superoxide in photosystem I, as well as the subsequent hydrogen peroxide and hydroxyl radical. Thereby if any transitory photooxidative stress is produced under these conditions it should be due mainly to the formation of singlet oxygen by triplet excited chlorophyll within the antenna. Since a-tocopherol is the main scavenger of singlet oxygen and lipid peroxy radicals, the large increase of this antioxidant within the species could be enough to compensate for the higher degree of photooxidative stress, playing an essential role in the survival of vegetation during the incidence of exceptional cold fronts in the Mediterranean region.

Diurnal changes in antioxidant and carotenoid composition in the Mediterranean schlerophyll tree Quercus ilex(L) during winter (Plant Science, 1999)
Seasonal changes of pigment composition and antioxidant content were characterized in the Mediterranean evergreen holm oak (Quercus ilex L.). Higher contents of antioxidants and carotenoids, with a photoprotective role during winter, indicated that this period was highly stressful, so a study of diurnal changes in photosynthesis, pigments and carotenoids was conducted during January in sun and shade leaves. Sun and shade leaves were used to compare the effects due only to low temperature separate from those resulting from the interaction of light. During winter, a relatively high rate of CO2 ﬁxation on sun leaves represented an important sink for photosynthetic electrons contributing to the annual carbon balance of the plant. This high rate contrasted with a reduced Fv :Fm, even at predawn. This reduction was correlated with the accumulation of zeaxanthin at the expense of violaxanthin by de-epoxidation. Sun leaves were also protected by a higher concentration of antioxidants (ascorbate, glutathione and tocopherol) and carotenoids (except lutein epoxide). Ascorbate was 10–50-fold greater than the other antioxidants, indicating a central role in protection against photooxidative stress. Nevertheless those mechanisms were unable to avoid a loss of hydrophilic antioxidants (glutathione and ascorbate) and xanthophylls during the initial morning hours after dawn, indicating that the ﬁrst target of photooxidative damage was these molecules

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.

Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.1667

Diurnal changes in photoprotective mechanisms in leaves of cork oak (Quercus suber) during summer (Tree Physiology, 1996)
Daily variations in photoprotective mechanisms were studied in sun and shade leaves of 40-year-old cork oak (Quercus suber L.) trees during early summer in Portugal. Although trees were not severely water stressed because predawn leaf water potentials remained high, photosynthesis and stomatal conductance decreased at midday. The midday depression in gas exchange was not reversed by short-term exposure to “optimal” conditions of temperature, light and vapor pressure deficit. Chlorophyll a fluorescence, maximum photochemical yield of photosystem II and the quantum yield of noncyclic electron transport showed midday depressions, but recovered by the evening. Both short-term changes in the components of the xanthophyll cycle (reversible de-epoxidation of violaxanthin during the day) as well as long-term changes (higher xanthophyll content in sun compared with shade leaves) were detected and may play a role in the dissipation of excess energy at midday. Because the activities of enzymes of the antioxidant system, superoxide dismutase and ascorbate peroxidase, were high enough to cope with the increase in oxygen reactive species likely to arise under the stressful conditions of midday, we conclude that these enzymes may provide an additional mechanism for energy dissipation.
10.1093/treephys/16.1-2.115